Synthesis and Physicochemical Investigations of Templated and Composite Zinc Oxide - Wan Nor Azmin, Wan Haizum (2011)
The diversity in shapes and dimensions as well as the hollow structures of zinc oxide (ZnO) from nano-to-microscale has attracted interests in its application as promising materials in driven to multifunctionality of performance and distinct domain of applications. Morphology-controlled synthesis of nano-to-micrometer dimensions of inorganic materials has become a routine in recent nanotechnology research efforts. Among several techniques attempted, templated synthesis approach is the most widespread route used by many scientists nowadays to prepare a wide variety of nanostructured and hollow-structured materials. However, this approach is usually complicated and requires stringent experimental conditions. Therefore, the use of microbial cells as templating agent is highly appealing. Nonetheless, to develop this facile and environmental-friendly method in preparing metal oxide particles still remains an insignificantly explored discipline. Another challenge in this materials research is also to find a proper way to overcome over the aggregation/agglomeration of ZnO particles with a minimum of chemicals used and more environmental-friendly products are produced. Nano- and micro-structured ZnO with specific shapes and dimensions was synthesized via hydrothermal method using live and dead Bacillus cereus bacterium as a biotemplating agent, without adjusting the pH of the system. ZnO particles with raspberry-, plate- and hollow rod-like particles have been successfully synthesized through this method and possible mechanism on the formation of ZnO structures have been proposed. Various volume ratios of metal ion solutions with respect to the bacterial suspensions have been studied to investigate their effects on the morphology architecture of ZnO nano/microparticles. Volume ratio at 20:10 was observed to be the optimum condition for biochemistry process to occur in the live bacterial cell for the formation of well-ordered ZnO nanostructures. On the other hand, volume ratio of 10:10 was found to be the ideal concentration for the construction of perfect hollow rod-like ZnO microparticles. The calcined sample of ZnO obtained from the biochemistry process occurring in live bacterial cell; shows that the raspberry-like structure is composed of 20-30 nm nodules and the plate-like structure has the thickness of about 25 nm as confirmed by FESEM micrographs. AFM 3D topographies and FT-IR elucidation confirmed that the reaction had occured between free Zn2+ cations and the deprotonated outer bacterial surface functional groups. The ZnO synthesized using dead bacterial cell as the biotemplating agent shows that the ZnO has nucleated on the dead B. cereus cell body during the hydrothermal reaction, before the sample was subjected to the heat treatment at 500 °C. These results show that the size and shape of the ZnO nano/microstructures would depend on the organelles that the zinc species were templated on and amount of zinc species introduced into the bacterial suspension system. Another topic investigated is the study on the behaviour of ZnO particles aggregation/agglomeration in ZnO/PVA polymer composite films prepared at various % (w/v) of PVA and different mass ratios of ZnO powder to PVA polymer without the use of organic capping agent as particle stabilizer. Several ZnO to polymer mass ratios have been prepared using commercial ZnO powder and water-soluble polymer, polyvinyl alcohol (PVA) via solution casting method. The thermal analyses (TGA-DTG and DSC) show that the thermal stability of polymer, PVA deteriorated after embedding ZnO particles and become significant when higher ZnO amount was incorporated into PVA matrix. From XRD of ZnO/PVA composite films, the observed diffraction intensities of ZnO and PVA phases were found to be depending on the particles aggregation and the contents of ZnO powder and PVA polymer. The band gap energy, Eg of the composite films obtained by UV-Vis analysis was found to decrease when the ZnO and PVA contents increased. This may be due to the formation of larger ZnO particles because of the high tendency of the particles to aggregate together. In addition, the possibility of ZnO particles could be well-dispersed inside PVA matrix is promising at relatively low ZnO and PVA contents. This was confirmed by visualization of ZnO distribution in the mass ratio of ZnO to PVA at 1:30 in 1% PVA matrix through TEM and ESEM micrographs.